Pemanfaatan Pelepah Pisang Sebagai Bio - Based Insulations Pada Ruang Akomodasi Kapal - Ike Dayi Febriana, Tristiandinda Permata, Aurista Miftahatul Ilmah (Politeknik Negeri Madura, 2019)
On the ship there is accommodation room that is used as a residence for the crew. Ship accommodation room generally consists of bedrooms, sanitary rooms, dining rooms, warehouses, the wheelhouse, and others. The construction of ship accommodation room must meet user safety and comfort standards. Alternative materials that can be used in the construction of ship accommodation room are bio-based insulation materials. Banana stem is a material that has the potential to be developed into bio-based insulations. In this research, a bonding method will be conducted by combining the banana stem with polyurethane. The results of this study are a tendency to decrease the thermal conductivity of bio-based insulation materials on the mass variation of banana stem.